Application of the Least Cost Analysis Method to Determine the Optimal Cost and Duration for Delayed Projects - Kumara, I Nyoman Indra; Tapa, I Gede Fery Surya; Indrashwara, Decky Cipta; Wedagama, Dewa Ayu Trisna Adhiswari; Srikandi, Melati Budi (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
The construction project of the Polresta Denpasar Multi-Purpose Building experienced delays due to the Eid al-Fitr holiday, resulting in a 9.35% setback, equivalent to 19 days. In the 20th week, the planned progress was 66.52%, but actual progress was only 57.17%. With 76 days remaining for the project's completion, the least cost analysis method was applied to find the optimal cost and time for completing the remaining work by increasing the workforce. This approach aims to ensure the project is completed on time and the contractor avoids penalties. The penalty is 1/1000 (1 ‰) of the contract value. The analysis used primary data such as interviews and project observations, and secondary data including contractor unit price analysis, budget plans (RAB), and S-curves. The data was analyzed from the remaining project work, crashing duration, to finding the cost slope for each task, and then using the least cost analysis method to determine the optimal cost and time. The analysis results showed that the optimized project cost after acceleration was Rp 3,077,713,130.90, with the project duration reduced from 76 days to 57 days, accelerated by 19 days. This acceleration saved costs by Rp 18,428,493.93. By applying this method, the project is expected to be completed faster without compromising quality, and the contractor can avoid delay penalties. This approach helps in time efficiency and budget management, ensuring all resources are used optimally and the project is completed on target.